A Study On Impact Of Digital Marketing In Customer Purchase In Chennai - CHERUKUR, MR.RAM BABU; PRIYA V, Ms. PADMA (The journal of contemporary issues in business and government, 2020)
The aim of this paper is to study digital marketing in consumer purchase decisions and to find out as to whether the consumers are aware of digital marketing and the digital channels influence in their purchase decision. The study is carried out through surveys from101 respondents. The results of the survey are analyzed using Regression .The findings revealed that customers are aware of digital marketing and shopping goods through digital channels in their purchase behaviour. The study is performed in a particular need to learn to meet global customers where they spend most of their time on the internet. So digital marketing helps you create brand awareness through channels such as social media ,e-mail,website,search engines to get the clear picture about the impact of digital marketing on customer purchase decisions.